Supreme ambition : Brett Kavanaugh and the conservative takeover - Marcus, Ruth (Simon & Schuster, 2019)
"Supreme Ambition is a page-turner that traces how Brett Kavanaugh deftly maneuvered to become the nominee; how he quashed resistance from Republicans who worried he was too squishy on conservative issues and from a president reluctant to reward a George W. Bush loyalist. It shows a Republican party that had concluded Kavanaugh was too big to fail, with senators and the FBI ignoring potentially devastating evidence against him. And it paints a picture of Democratic leaders unwilling to engage in the no-holds-barred partisan warfare that might have defeated the nominee. In the tradition of The Brethren and The Power Broker, Supreme Ambition is the definitive account of a pivotal moment in modern history, one that was thirty years in the making and that will shape the judicial system of America for generations to come." -- Amazon.com